2020
DOI: 10.5653/cerm.2019.03188
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin C on the gene expression profile of sperm protamines in the male partners of couples with recurrent pregnancy loss: A randomized clinical trial

Abstract: Objective: Since sperm abnormalities are known to be a major reason for recurrent pregnancy loss (RPL), any defects in DNA structure and chromatin condensation can place embryos at risk in the early stage of development and implantation. As antioxidants such as vitamin C may play a protective role against the destruction of protamine genes in sperm chromatin, this study was conducted to evaluate the effects of vitamin C on chromatin and the expression of protamine genes in the male partners of couples with RPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…A total of 21 articles published between January 2019 and July 2020 investigated the effects of antioxidant treatment on semen quality ( Table 4 ) [ 25 42 43 44 45 46 56 57 92 93 94 95 96 97 98 99 100 101 104 115 121 ]. Based on our analysis, 13 and 8 studies were ranked as low and high-quality, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 21 articles published between January 2019 and July 2020 investigated the effects of antioxidant treatment on semen quality ( Table 4 ) [ 25 42 43 44 45 46 56 57 92 93 94 95 96 97 98 99 100 101 104 115 121 ]. Based on our analysis, 13 and 8 studies were ranked as low and high-quality, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Terai et al [ 98 ] did not include a placebo group, with an experimental group investigating a Chinese herbal formula. Hadi et al [ 45 ], Alahmar et al [ 97 ], Hamidian et al [ 121 ], Salehi et al [ 42 ], Hasoon [ 43 ], Gambera et al [ 93 ], Arafa et al [ 25 ], Nazari et al [ 101 ], and Jannatifar et al [ 92 ] all reported improved semen parameters, but these studies are uncontrolled open label trials and are relatively underpowered. Furthermore, Alkumait et al [ 100 ] and Terai et al [ 98 ] were unblinded trials with relatively small sample sizes (n=51 and 31, respectively).…”
Section: Critical Evaluation Of the Necessity Of Additional Double-blmentioning
confidence: 99%
“…It has been associated with improvements in semen quality in a dose-dependent manner in smokers [ 35 ], whereas the main benefits seem to lie on motility [ 36 ]. Furthermore, meaningful effects of vitamin C administration on DNA quality and mRNA levels on the semen of patients with recurrent pregnancy loss have been observed [ 37 ]. In patients with varicocele, increased oxidative stress markers have been found to be negatively associated with the concentration of vitamin C in the internal spermatic vein [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This randomized clinical trial was designed as an alternative investigation of our previous study that was registered in the Iranian Registry of Clinical with the national ID no. IRCT20180312039059N1 [ 18 ]. Twenty male partners of infertile couples with RPL due to male factor infertility were randomly selected among who referred to Yazd Research and Clinical Center for infertility using a random number table.…”
Section: Methodsmentioning
confidence: 99%